Patient Portals as Facilitators of Engagement in Patients With Diabetes and Chronic Heart Disease: Scoping Review of Usage and Usability - Benjamin Scheckel; Katharina Schmidt; Stephanie Stock; Marcus Redaèlli (JMIR Publications, 2023)
BackgroundPatient portals have the potential to improve care for chronically ill patients by engaging them in their treatment. These platforms can work, for example, as a standalone self-management intervention or a tethered link to treatment providers in routine care. Many different types of portals are available for different patient groups, providing various features. ObjectiveThis scoping review aims to summarize the current literature on patient portals for patients with diabetes mellitus and chronic heart disease regarding usage behavior and usability. MethodsWe conducted this review according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) statement for scoping reviews. We performed database searches using PubMed, PsycInfo, and CINAHL, as well as additional searches in reviews and reference lists. We restricted our search to 2010. Qualitative and quantitative studies, and studies using both approaches that analyzed usage behavior or usability of patient portals were eligible. We mapped portal features according to broad thematic categories and summarized the results of the included studies separately according to outcome and research design. ResultsAfter screening, we finally included 85 studies. Most studies were about patients with diabetes, included patients younger than 65 years, and were conducted in the United States. Portal features were categorized into educational/general information, reminder, monitoring, interactivity, personal health information, electronic/personal health record, and communication. Portals mostly provided educational, monitoring, and communication-related features. Studies reported on usage behavior including associated variables, usability dimensions, and suggestions for improvement. Various ways of reporting usage frequency were identified. A noticeable decline in portal usage over time was reported frequently. Age was most frequently studied in association with portal use, followed by gender, education, and eHealth literacy. Younger age and higher education were often associated with higher portal use. In two-thirds of studies reporting on portal usability, the portals were rated as user friendly and comprehensible, although measurement and reporting were heterogeneous. Portals were considered helpful for self-management through positive influences on motivation, health awareness, and behavioral changes. Helpful features for self-management were educational/general information and monitoring. Barriers to portal use were general (eg, aspects of design or general usability), related to specific situations during portal use (eg, login procedure), or not portal specific (eg, user skills and preferences). Frequent themes were aspects of design, usability, and technology. Suggestions for improvement were mainly related to technical issues and need for support. ConclusionsThe current state of research emphasizes the importance of involving patients in the development and evaluation of patient portals. The consideration of various research designs in a scoping review is helpful for a deeper understanding of usage behavior and usability. Future research should focus on the role of disease burden, and usage behavior and usability among older patients.